IRMS delta values (13C) of nandrolone and testosterone products available in the UK: Implications for anti‐doping. Issue 11 (3rd December 2018) - Brailsford, Alan D.; Majidin, Wan Noor Mahirah; Wojek, Nick; Cowan, David A.; Walker, Christopher
Abstract: Anabolic androgenic steroids (AAS) are the most widely abused class of drugs by athletes and thus represent a significant problem to the anti‐doping community. Confirmation of a doping violation for AAS cannot always be based on their presence alone due to the endogenous production of some steroids. Both testosterone (and its metabolites) and the major diagnostic metabolite of nandrolone (19‐norandrosterone) are produced endogenously. Gas chromatography–combustion–isotope ratio mass spectrometry (GC–C–IRMS) is used in such cases to differentiate between the administration of a synthetic preparation and endogenous steroid production by measurement of their differing carbon isotope ( 13 C/ 12 C) ratio. The purpose of this study was to investigate the availability of steroid preparations in the UK with a 13 C content analytically indistinguishable from that of endogenous steroids. Fourteen preparations containing nandrolone ( n  = 9) and testosterone ( n  = 5) were analyzed. The δ 13 C values were determined using GC–C–IRMS and the identity of the steroid preparations was confirmed using gas chromatography–mass spectrometry (GC–MS). Ten steroid preparations displayed δ 13 C values within the range expected for synthetic steroids (less than −27‰). However, four nandrolone preparations displayed δ 13 C values that overlap with the values considered to be endogenous in origin (range: −26 to −16‰). Misuse of these preparations could prevent the confirmation of nandrolone administration using GC–C–IRMS in anti‐doping cases. Abstract : Discovery of nandrolone preparations with "endogenous‐like" 13 C delta values available in the UK market.